PRIORITY DIRECTIONS OF ESTABLISHING THE ACTIVITY OF FREE ECONOMIC ZONES IN UZBEKISTAN - Iskandarova Dilorom Khayrullayevna (American Journals, 2023)
The article examines the priority directions for the establishment of free economic zones in Uzbekistan. Also, the formation of legal norms for foreign direct investments in accordance with international standards, attracting more investments to the country's economy, structural changes in the economy. Proposals and recommendations on the establishment of SEZs and increasing investment activity in them were formulated.
Keywords: Investment, investment attractiveness, action strategy, potential, market conjuncture, strategic program, economic zone, industrial zone.